Freeing speech : the constitutional war over national security - Denvir, John, 1942- (New York : New York University Press, 2016)
John Denvir proposes an ambitious solution to the problem of how the constitution impacts national security: a First Amendment that ensures the voices of opposition are heard.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: United States; War and emergency legislation -- United States; Freedom of speech -- United States; National security -- United States; Law; United States of America, USA; Political science & theory; Laws of specific jurisdictions & specific areas of law; Constitutional & administrative law: general